Longer aftershocks duration in extensional tectonic settings. Issue 1 (December 2017) - Valerio, E.; Tizzani, P.; Carminati, E.; Doglioni, C.
Abstract Aftershocks number decay through time, depending on several parameters peculiar to each seismogenic regions, including mainshock magnitude, crustal rheology, and stress changes along the fault. However, the exact role of these parameters in controlling the duration of the aftershock sequence is still unknown. Here, using two methodologies, we show that the tectonic setting primarily controls the duration of aftershocks. On average and for a given mainshock magnitude (1) aftershock sequences are longer and (2) the number of earthquakes is greater in extensional tectonic settings than in contractional ones. We interpret this difference as related to the different type of energy dissipated during earthquakes. In detail, (1) a joint effect of gravitational forces and pure elastic stress release governs extensional earthquakes, whereas (2) pure elastic stress release controls contractional earthquakes. Accordingly, normal faults operate in favour of gravity, preserving inertia for a longer period and seismicity lasts until gravitational equilibrium is reached. Vice versa, thrusts act against gravity, exhaust their inertia faster and the elastic energy dissipation is buffered by the gravitational force. Hence, for seismic sequences of comparable magnitude and rheological parameters, aftershocks last longer in extensional settings because gravity favours the collapse of the hangingwall volumes.